Production of an Innovative, Surface Area‐Enhanced and Biodegradable Biofilm‐Generating Device by 3D Printing - Atulona Datta; Rituparna Saha; Sovan Sahoo; Arup Ratan Roy; Shayontani Basu; Girish Mahajan; Subhash Chandra Panja; Joydeep Mukherjee (Engineering in Life Sciences)
ABSTRACT The enhanced surface cylindrical flask (ESCF) consists of an eight‐striped inner arrangement holding 16 standard microscopic slides placed inside a cylindrical vessel. The specially designed spatula‐accessible slides can be withdrawn from the vessel during cultivation without disturbing biofilm formation through an innovative window‐flap accessibility mechanism. The vessel and its accessories were three‐dimensional (3D) printed by applying a fused deposition modeling technique utilizing biodegradable polylactic acid. Biofilms of clinically relevant bacteria namely Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli were successfully grown in the ESCF and observed through confocal laser scanning microscopy. Advantages of the device include an enhanced surface area for biofilm formation, ease of insertion and removal of microscopic slides, convenient fitting into standard rotary shaker platforms, creation of anoxic/microaerophilic environment inside the vessel as well as the feasibility of pH, dissolved gases, and metabolite measurements in the liquid surrounding the biofilm. The ESCF will find widespread application in medical, industrial, and environmental disciplines.